Hepatitis B: A Pilot study on awareness and attitude among staff nurses and students of a teaching hospital in India - Ramandeep Singh Gambhir; Ridhi Aggarwal; Aanchal Gupta; Satinder Singh Walia; Nupur Hingad; Garish Kumar (National Institute of Public Health - National Institute of Hygiene, 2024)
Background Hepatitis B is a serious public health concern and health care professionals especially nurses are at higher risk of acquiring this infection. Basic knowledge, awareness and a positive attitude are required to prevent this disease. Objective The present pilot study was conducted to assess awareness and attitude regarding hepatitis B among staff nurses and nursing students of a teaching hospital in north India. Material and Methods A total of 205 subjects who gave consent to participate were included in this descriptive study. A self-structured pre-tested close ended questionnaire comprising of two parts was used to collect information from the study subjects. First part collected information on demographic details of the study subject and second part assessed subjects' awareness and attitude on various aspects of hepatitis B infection including vaccination. Chi-square test and multiple linear regression analysis was used for statistical analysis. Results The mean age of the study subjects was 25.8±5.6 years. Awareness regarding HBV infection was present among 92.6% (190) of subjects. Long-term effects of hepatitis B were known to 58.4% (119) of subjects and 79.1% (162) of subjects reported taking universal precautions. Half of the subjects (105), were getting regularly tested for hepatitis B antigen.The odds of getting regularly tested for hepatitis B antigen were 3.26 times greater in female subjects and 3.45 times greater in subjects who were GNMs. Conclusion Low awareness levels were reported regarding some important aspects of hepatitis B among study subjects though more than 90% were aware of it. There is an urgent need for education and training programs for nurses designed to increase their knowledge about HBV infection.